Local anesthetics injection therapy for musculoskeletal disorders: a systematic review and meta-analysis - Moßhammer, Dirk; Mayer, Benjamin; Joos, Stefanie (The clinical journal of pain, 2013)
Objectives: - Therapeutic injections with local anesthetics (TLA) are widespread and are used for various symptoms of the musculoskeletal system. The aim of the present project was to evaluate the efficacy and safety of TLA in the treatment of musculoskeletal disorders. - Methods: - Systematic literature search for controlled clinical trials (Medline, Cochrane, CAMbase, hand search of references) without language limitation; independent screening of the search results (n=3200 hits), abstract reading, and full-text analysis by 2 reviewers. Two authors independently extracted the data and assessed study quality. Meta-analysis was calculated for studies using a continuous scale for pain assessment. - Results: - Twenty-four controlled trials were included in this review. In almost all studies no primary outcome measure was defined and the overall study quality was low. The qualitative data analysis revealed no clear trend for or against TLA. The meta-analysis of 12 studies showed no significant difference in pain reduction for TLA compared with control treatments consisting of saline injections or other substances, oral analgesics, or nonpharmacological interventions (standardized mean difference −0.31, 95% confidence interval, −0.75 to 0.14). Minor adverse side effects were reported in 7 studies in both the TLA and the control groups with no trend for one of the groups to be safer. - Discussion: - Despite the widespread use of TLA for musculoskeletal disorders in daily practice, available data are sparse and of low quality and, therefore, do not allow a final recommendation. High-quality studies are needed to close the gap between common practice and research.
Gesehen am 15.06.2021